DESIGN AND ANALYSIS OF CONNECTING ROD OFDISCONNECTOR BASED ON ANSYS WORKBENCH - OUYANG ZhenGuo; MA ZongXiong; YOU YiMin; LI Jia; XIAO LiangXian (Jixie qiangdu)
a combination method of simulation and test data to solve the material parameters was raised,with the certain material parameters a new type of connecting rod of disconnector was analyzed.Material‘s Young modulus and Poisson’s ratio was obtained by using the existing connecting rod of disconnector.The model of new type of connecting rod of disconnector was made by the software of Solidworks.The finite element software of Ansys Workbench was used to carry out linear static structural analysis.The simulation result provides a theoretical basis for design and analysis new type of connecting rod of disconnector.